2006
DOI: 10.1186/1475-2875-5-61
|View full text |Cite
|
Sign up to set email alerts
|

Who sleeps under bednets in Ghana? A doer/non-doer analysis of malaria prevention behaviours

Abstract: Background: Malaria prevention programmes should be based in part on knowledge of why some individuals use bednets while others do not. This paper identifies factors and characteristics of women that affect bednet use among their children less than five years of age in Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
56
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 21 publications
13
56
0
1
Order By: Relevance
“…being rained on, eating sugar cane, or lack of hygiene cause malaria) which combined with impoverishment leads to ineffective malaria prevention. Misconceptions relating to malaria found in this study were remarkably similar to those found elsewhere in Africa [70-75] and other parts of the world [26,76,77]. The findings show that there is a high level of what community members term as 'western knowledge' in the Rusinga community which is not completely trusted and, therefore, high priority is still given to traditional beliefs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…being rained on, eating sugar cane, or lack of hygiene cause malaria) which combined with impoverishment leads to ineffective malaria prevention. Misconceptions relating to malaria found in this study were remarkably similar to those found elsewhere in Africa [70-75] and other parts of the world [26,76,77]. The findings show that there is a high level of what community members term as 'western knowledge' in the Rusinga community which is not completely trusted and, therefore, high priority is still given to traditional beliefs.…”
Section: Discussionsupporting
confidence: 83%
“…This provides an excellent base for increased training on bednet use and availability of nets to protect the target population and reach the Abuja target [80]. In agreement with other studies [75,81,82] bednet ownership was primarily dependent on the socio-economic status of the household. They are luxury assets which are there in better-off households even if the family might have limited knowledge on malaria.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Knowledge on the use of ITN as a preventive measure against mosquito bites was found to be significantly higher among respondents in this follow-up study compared to the baseline survey (Table 3) [15]. This level of knowledge on preventive use of ITN has also been observed in Colombia [19], Nepal [20], Eritrea [9], and Ghana [21] while a lower level of knowledge was observed in India [22], Iran [23] and Turkey [24]. …”
Section: Discussionsupporting
confidence: 55%
“…In Nigeria, more than 80 % of respondents had never purchased any form of ITN (Onwujekwe et al 2005), while a report submitted that less than 20 % of households own ITNs WHO 2011). Even where there is a high level of knowledge regarding the benefits of ITNs (in Ghana), it does not translate to a high level of usage (De La Cruz 2006;). However, there has been progress in some countries.…”
Section: Malaria Prevention and Treatmentmentioning
confidence: 97%